2022
DOI: 10.1038/s42003-022-04161-7
|View full text |Cite
|
Sign up to set email alerts
|

The Staphylococcus aureus cell division protein, DivIC, interacts with the cell wall and controls its biosynthesis

Abstract: Bacterial cell division is a complex, dynamic process that requires multiple protein components to orchestrate its progression. Many division proteins are highly conserved across bacterial species alluding to a common, basic mechanism. Central to division is a transmembrane trimeric complex involving DivIB, DivIC and FtsL in Gram-positives. Here, we show a distinct, essential role for DivIC in division and survival of Staphylococcus aureus. DivIC spatially regulates peptidoglycan synthesis, and consequently ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 71 publications
1
14
0
Order By: Relevance
“…Cell fractionation preparation was performed as previously described ( 43 ), with minor modifications. Strains of interest were assessed in biological triplicate and grown overnight in 3 mL TSB for 18 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Cell fractionation preparation was performed as previously described ( 43 ), with minor modifications. Strains of interest were assessed in biological triplicate and grown overnight in 3 mL TSB for 18 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…MurJ is important for the recruitment of PG synthesis from the cell periphery to the septum due to the lipid II‐affinity of the PG biosynthesis proteins (Monteiro et al, 2018 ). DivIB and DivIC are cell wall‐binding proteins that also seem to have distinct functions at this checkpoint (Tinajero‐Trejo et al, 2022 ). Recently it was shown that DivIC has a role in recruiting the PG synthetases PBP2 and FtsW to the division septum, and interestingly, this was shown to depend on the binding of the extracellular domain of DivIC to WTA in the cell wall, suggesting that there may be chemical or architectural characteristics of the cell wall (PG and/or WTA) that is needed to allow further progression of septal synthesis (Tinajero‐Trejo et al, 2022 ).…”
Section: The Stages Of Cell Divisionmentioning
confidence: 99%
“…DivIB and DivIC are cell wall‐binding proteins that also seem to have distinct functions at this checkpoint (Tinajero‐Trejo et al, 2022 ). Recently it was shown that DivIC has a role in recruiting the PG synthetases PBP2 and FtsW to the division septum, and interestingly, this was shown to depend on the binding of the extracellular domain of DivIC to WTA in the cell wall, suggesting that there may be chemical or architectural characteristics of the cell wall (PG and/or WTA) that is needed to allow further progression of septal synthesis (Tinajero‐Trejo et al, 2022 ). In addition, it was found that the arrival of MurJ to the septum corresponds to the time point during cytokinesis when the Z ring constriction rate increases (Figure 1d,e ).…”
Section: The Stages Of Cell Divisionmentioning
confidence: 99%
“…Therefore, the lengthening of this division stage likely drives the increase in cell size observed in the mutant, while in a small number of cases (Suppl. A lack of proteins involved in cell division or cell wall synthesis frequently causes an increase in cell size (Cheng, Missiakas and Schneewind, 2014;Do et al, 2020;Tinajero-Trejo et al, 2022;Wacnik et al, 2022). For example, deletion mutants of the genes encoding for UgtP or LtaA, proteins responsible for the lipoteichoic acid (LTA) glycolipid anchor synthesis and flipping (Gründling and Schneewind, 2007a) display longer LTA structures, enlargement of cell size, defects in septa formation and higher susceptibility to lytic enzymes (Hesser, Schaefer, et al, 2020).…”
Section: Resultsmentioning
confidence: 99%